Cluster Projective Synchronization of Fractional-Order Complex Network via Pinning Control. (12th May 2014) - Yang, Li-xin; He, Wan-sheng; Zhang, Fan-di; Jia, Jin-ping
Abstract : Synchronization is the strongest form of collective phenomena in complex systems of interacting components. In this paper, the problem of cluster projective synchronization of complex networks with fractional-order nodes based on the fractional-order differential equation stability theory is investigated. Only the nodes in one community which have direct connections to the nodes in other communities are controlled. Some sufficient synchronization conditions are derived via pinning control. Numerical simulations are provided to show the effectiveness of the theoretical results.